Analisis Minat Pelaku Usaha General Trade Terhadap Penggunaan Aplikasi Belanja Online B2B (Studi Dengan Pendekatan Unified Theory of Acceptance and Use of Technology) - Weni Novandari; Diah Setyorini Gunawan; Icuk Rangga Bawono; Rifda Naufalin; Sri Maryani; Jajang Jajang (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2022)
Traditional markets (general trade), still have an important place, especially for Indonesian people who live in suburban areas, in sub-districts and in rural areas. Although now its existence is starting to be shifted by modern markets, however, there are many and spread in various regions, making the contribution of traditional markets to the Indonesian economy cannot be ignored. So that there are efforts from various parties, to improve the marketing performance of business actors in this traditional market, including the introduction of technology. The purpose of this study is to analize the acceptance of traditional retail business actors towards online shopping applications for B2B consumers, in terms of Performance Expectancy, Effort expectancy, Social Influence and Facilitating Conditions variables. The sample of this research is 161 traditional retail business actors, which include owners of traditional stalls, grocery stores and kiosks. Analysis of research data using Partial Least Suare (PLS) analysis tool. The results showed that Performance Expectancy, Social Influence and Facilitating Conditions had a positive effect on intention in using B2B online shopping applications. Meanwhile, Effort Expectancy has no effect on intention in using B2B online shopping applications. The results of this study are expected to be used as considerations for formulating various strategies and policies to improve technological literacy for business actors to improve their business performance, so that their contribution to the performance of national economic recovery can be optimal. Keywords: B2B Online Shopping Application, General Trade, Unified Theory of Acceptance and Use of Technology (UTAUT)